Antiproliferative, proapoptotic, and antimigration activities of marine sponges against human colon cancer cell line (HCT116) - Aileen May G. Ang, Sharon Rose M. Tabugo, Mylene M. Uy (Journal of Applied Pharmaceutical Science, 2023)
Marine sponges’ anticancer potential relies on various cellular and molecular pathways. Agelas sp., Ircinia sp., and Petrosia weinbergi were collected off the coast of Iligan Bay, Misamis Oriental, Philippines. The antiproliferation, proapoptotic, and antimigration properties of their hexane (H), dichloromethane (DCM), and methanol: water (MW) extracts against Human colorectal carcinoma cell line (HCT116) carcinoma cells were investigated using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT), Caspase-Glo® 3/7, and in vitro scratch wound assay, respectively. The extracts exhibited cytotoxicity against HCT116. The viability of the treated cells was significantly lower (p < 0.05) than the negative control. Treatment of the HCT116 with MW and DCM extracts of P. weinbergi and DCM extract of Ircinia sp. resulted in a statistically higher (p < 0.05) luminescence than the negative control. Relative to dimethyl sulfoxide, the extracts increased caspase-3/7 activity more than onefold. This suggests the proapoptotic activity through the activation of the caspase-3/7. Lastly, the MW extract of Ircinia sp. and the H extract of P. weinbergi significantly (p < 0.05) inhibited the migration of HCT116 after wounding. Thus, Ircinia sp. and P. weinbergi were found to show potential antiproliferative, proapoptotic, and antimigration properties against HCT116. Further investigation of compounds and the mechanism of action involved in their anticancer property are thus recommended.